2015
DOI: 10.1177/1461355714566777
|View full text |Cite
|
Sign up to set email alerts
|

The Royal Malaysia Police has got its strategy wrong

Abstract: The Malaysian police appealed to parliament to reinstate preventive detention without trial laws, such as the Emergency Ordinance and the Prevention of Crime Act 1959, to reduce crimes. These laws were abolished in 2012 because they violate the rights of ‘innocent until proven guilty’ and have been abused. Although the legal profession and civil society disagreed with their reinstatement, parliament amended the Prevention of Crime Act in 2013. This article shows that such laws alone have not been effective in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Regardless, there have been criticisms of the RMP. One study found that promulgating new laws for enforcement by the police were, by themselves, not effective in reducing crime (Teh, 2015). Farrar (2013, p. 232) noted that detractors of the RMP have remarked on its unfortunate tendency to serve as “the executive right arm” of the Federal Government with little organizational autonomy.…”
Section: Malaysia and Its Policementioning
confidence: 99%
“…Regardless, there have been criticisms of the RMP. One study found that promulgating new laws for enforcement by the police were, by themselves, not effective in reducing crime (Teh, 2015). Farrar (2013, p. 232) noted that detractors of the RMP have remarked on its unfortunate tendency to serve as “the executive right arm” of the Federal Government with little organizational autonomy.…”
Section: Malaysia and Its Policementioning
confidence: 99%